Carboxylic Acid Salts as Dual‐Function Reagents for Carboxylation and Carbon Isotope Labeling. (26th February 2023) - Wang, Shuo; Larrosa, Igor; Yorimitsu, Hideki; Perry, Gregory J. P.
Abstract: The potassium salts of carboxylic acids are developed as efficient carboxylating agents through CO2 exchange. We describe these carboxylates as dual‐function reagents because they function as a combined source of CO2 and base/metalating agent. By using the salt of a commercially available carboxylic acid, this protocol overcomes difficulties when using CO2 gas or organometallic reagents, such as pressurized containers or strictly inert conditions. The reaction proceeds under mild conditions, does not require transition metals or other additives, and shows broad substrate scope. Through the preparation of several biologically important molecules, we show how this strategy provides an opportunity for isotope labeling with low equivalents of labeled CO2 . Abstract : The potassium salt of triphenylacetic acid is developed as a combined source of CO2 and base/metalating agent. This method avoids specialized equipment and is used in the carboxylation of a range of compound classes. This provides a mechanistically distinct approach to carboxylation that has also been applied in carbon isotope labeling.